Implementation of Local Government Organizations According to the Adolescent Pregnancy Prevention and Solution Act 2016 : Case Study of Health Region 10, Thailand - Sopapan Kaewhan; Saksit Sripa (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Pregnancy in adolescence is a global problem. Around the world gives attention and attempts tofind a solution in prevention and resolution of the problem. The purpose of this research is to learn the process ofthe local authorities in complying act for prevention and solution of the adolescent pregnancy problem, B.E. 2559(2016) : case studies of Health Region 10. Methods: The study was divided into 2 parts is Quantitative research.It is a cross-sectional survey study by questionnaire and interviewingwhich are methods to collect data, analyzinginformation, using descriptive statistics including frequency, percentage, mean, standard deviation to describe theinformation of the personal factor, knowledge, comprehensive, attitude, point of views, problems and berriers tothe process of act for prevention and solution of the adolescent pregnancy problem, B.E. 2559 (2016). The sampleand using Pearson correlation coefficient analyze the relationships between variables Operate between August andOctober 2020.Results: The result of the research found that in phase 1 the general information of people who workin reproductive health, the local authorities in complying act for prevention and solution of the adolescent pregnancyproblem, B.E. 2559 (2016) : case studies of Health Region 10 doing survey is women 66.80 percentage, age 36 –45 years 51.60 percentage, mostly working in Subdistrict Administrative Organization 64.80 percentage, years ofworking mean 10.74 years the score of knowledge personnel about act for prevention and solution of the adolescentpregnancy problem, B.E. 2559 (2016) is high level ( X = 8.38 score, S.D. = 2.10) and the score of Comprehensivemedium level ( X =7.42 score, S.D. = 1.32). The people who work in reproductive health the local authoritiescomplying pay attention in pregnancy in adolescent 54.30 percentage, comprehensive and attitude is high level ( X=3.70 score, S.D. = 0.50). In the Phase 2, the analysis of Pearson Correlation Coefficient) analyzed to the relationshipbetween variables found that the knowledge of the act for prevention and solution of the adolescent pregnancyproblem, B.E. 2559 (2016) (X1) (r=0.164*), the attitude and emphasis about act for prevention and solution of theadolescent pregnancy problem, B.E. 2559 (2016) (X3) (r=0.214*) and the point of views in people who work in thelocal authorities complying act for prevention and solution of the adolescent pregnancy problem, B.E. 2559 (2016)(X4) (r=0.369*) have positive relationship with the result of the process in a problem and a barrier in operations ofthe relevant departments according to act for prevention and solution of the adolescent pregnancy problem, B.E.2559 (2016), statistically significant at a level of 0.05. The understanding of act for prevention and solution of theadolescent pregnancy problem, B.E. 2559 (2016) (X2) (r=-0.108) does not have any relationship with the results ofthe process in a problem and a barrier in the operations of the relevant departments according to act for preventionand solution of the adolescent pregnancy problem, B.E. 2559 (2016), statistically significant at a level of 0.05.Conclusion: In conclusion, this research shows the highest score in Yasothorn province that using strategy of Acttheprevention and resolving of pregnancy in adolescence B.E. 2559 following 5 strategies and added strategy number 6which are religious and culture. Building a family culture of conduct living in adolescents based on traditions in dailylife under the supervision of their parents has been operating models that are suitable for the local. Therefore, thesuccess factor of the operation of Health Region 10 and institution relevant should be given priority by formulatinga policy to lead to further action.